GIS application for school information and management system - Ismail, Zamri; Said, Mohamad Nor (UTM, 2004)
In line with the development of the whole wide world which is focusing on the information technology era, the Geographic Information System applications acts as an important tool in problem solving and decision making. Thus, a GIS application for school information and management system was developed for Sekolah Kebangsaan Sri Skudai in order to facilitate the management and administration of the school. This is due to certain problems faced by the school that arise from the manually conducted management and administration process. There is also a lack of an ideal system that is able to integrate all the attribute and spatial data for planning and management. Other than that, the basic and additional data of the school is usually stored in a lot of different places, making it hard for the school when the combination and integration of these data is needed to deal with certain problems or situations. Therefore, this research was conducted in order to develop an information system that plans and manages the administration of Sekolah Kebangsaan Sri Skudai through the ArcView 3.2 software, and also to study the effectiveness of its application. The development of this system starts off with conducting a user requirement study, designing a database, data collection, database development and testing the database. In the end, the GIS application for school information and management system for Sekolah Kebangsaan Sri Skudai was developed.